Correlation of knowledge, attitude, and family support with wound care of post sectio caesaria patients in Sejiran Setason Hospital West Bangka Regency - Riza Savita; Rezka Nurvinanda (Universitas 'Aisyiyah Yogyakarta, 2022)
Wound care in post Sectio Caesaria (SC) patients is one of the external factors that are very important for the wound healing process. After returning home, the post-SC mother still has to take care of the wound so as not to cause infection. Data on childbirth through SC at Sejiran Setason Hospital, West Bangka, was recorded in as much as 48% of 658 deliveries in 2018. This study aimed to determine the relationship between knowledge, attitudes, and family support with post sectio caesaria wound treatment at Sejiran Setason Regional Hospital, West Bangka Regency in 2019. The study was conducted using a cross-sectional design. The population in this study was all mothers who had experienced sectio caesaria at Sejiran Setason Hospital, with as many as 368 patients. The sample taken in this study was 86 respondents who met the inclusion criteria. Sampling uses quota sampling techniques, while hypothesis testing uses spearman rank (rho). The results showed the relationship of knowledge ( p = 0.026;r = 0.240*) and attitude (p = 0.011; r = 0.273*) with the care of post-SC patient wounds. In the variable family support, the result was p=0.782 α (0.05), which means that there is no relationship. For this study, it is hoped that health workers can improve post-SC wound care education to patients and provide resume returns to improve mothers' knowledge and attitudes in caring for post-SC wounds.